2007
DOI: 10.1161/circulationaha.106.629428
|View full text |Cite
|
Sign up to set email alerts
|

Is Dual-Chamber Programming Inferior to Single-Chamber Programming in an Implantable Cardioverter-Defibrillator?

Abstract: Background-The INTRINSIC RV (Inhibition of Unnecessary RV Pacing with AVSH in ICDs) study tested the hypothesis that dual-chamber rate-responsive (DDDR) with atrioventricular search hysteresis (AVSH) 60-130 programming is not inferior to single-chamber (VVI)-40 programming in an implantable cardioverter defibrillator with respect to all-cause mortality and heart failure hospitalizations using an equivalence margin of 5%. Methods and Results-At 108 centers, 1530 patients with an implantable cardioverter defibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(43 citation statements)
references
References 33 publications
(25 reference statements)
2
40
0
1
Order By: Relevance
“…Within the DDDR-70 group, there were more cardiac events when the percentage of ventricular pacing exceeded 40% (P ¼.09) compared with patients with 95% RV stimulation (DDDR-70) or [31,32] However, a more detailed post hoc analysis of the Inhibition of Unnecessary RV Pacing With AtrialVentricular Search Hysteresis in ICDs (INTRINSIC RV) trial revealed that the most favorable clinical results were not in the VVI groups with the least percentage of RV pacing but in the subgroup that had DDD pacing with longer atrioventricular delays and 11%-19% of ventricular pacing. This parameter selection probably helped patients to avoid exceedingly low heart rates while preserving intrinsic atrioventricular conduction most of the time [31,33]. In the Second Multicenter Automated Defibrillator Implantation Trial (MADIT II), a higher risk of HF was observed in patients who had a greater than 50% burden of RV pacing [34].…”
Section: Right Ventricular Pacingmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the DDDR-70 group, there were more cardiac events when the percentage of ventricular pacing exceeded 40% (P ¼.09) compared with patients with 95% RV stimulation (DDDR-70) or [31,32] However, a more detailed post hoc analysis of the Inhibition of Unnecessary RV Pacing With AtrialVentricular Search Hysteresis in ICDs (INTRINSIC RV) trial revealed that the most favorable clinical results were not in the VVI groups with the least percentage of RV pacing but in the subgroup that had DDD pacing with longer atrioventricular delays and 11%-19% of ventricular pacing. This parameter selection probably helped patients to avoid exceedingly low heart rates while preserving intrinsic atrioventricular conduction most of the time [31,33]. In the Second Multicenter Automated Defibrillator Implantation Trial (MADIT II), a higher risk of HF was observed in patients who had a greater than 50% burden of RV pacing [34].…”
Section: Right Ventricular Pacingmentioning
confidence: 99%
“…Clinical trials and simulated testing of induced arrhythmias that compared single-vs dual-chamber discriminators have reported inconsistent results [10,33,[137][138][139]. Two meta-analyses found no superiority of dual-chamber ICDs in terms of mortality or inappropriate therapies [11,140].…”
Section: Dual-chamber Vs Single-chamber Algorithmsmentioning
confidence: 99%
“…Similarly, clinical trials comparing settings that simulate a single‐chamber device with settings that utilize both leads among patients who have all received dual‐chamber devices are also conflicting 14, 15, 16, 17. A limitation and one potential explanation for the variable results of these trials is that they included patients who received an ICD for secondary prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Dual‐chamber ICDs may have enhanced arrhythmia discrimination, which, in theory, might reduce inappropriate shocks caused by supraventricular tachycardia. However, existing data regarding the benefits of dual‐chamber devices with respect to inappropriate therapies are inconclusive 10, 11, 12, 13, 14, 15, 16, 17…”
Section: Introductionmentioning
confidence: 99%
“…While several studies have compared outcomes between single-chamber and dual-chamber ICDs, these investigations had major limitations, yielded conflicting results, and predated the evidence on optimal programming of ICDs. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Today's health care providers and patients, therefore, often struggle in making the critical decision of what device type to choose, and professional societies and policymakers are incapable of developing evidence-based recommendations and coverage decisions. 8,33 These issues are further compounded by the advent of subcutaneous ICDs, whose outcomes, especially in the elderly, are uncertain.…”
Section: Professional Societies/ Researchersmentioning
confidence: 99%